The effect of intensive training on bone metabolism in disabled male swimmers - Guo, Y.; Ding, H.; Tang, D. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The impact of intensive aerobics on bone metabolism of male swimmers with disabilities was explored. This study observed changes in relevant indicators of bone metabolism during long-term intensive swimming training. Methods Ten male disabled swimmers from the Chinese National Team were selected for the study. Measures were conducted on such indicators as blood calcium (Ca), alkali phosphates (AKP), tartrate-resistant acid phosphates (Stracp), and urine calcium (U-Ca), creatinine and hydroxyproline (U-HOP) for three months. Results After 3-months of intensive training, blood alkali phosphates in the swimmers improved dramatically (p<0.01), blood tartrate-resistant acid phosphatase was lowered (p<0.05), blood calcium was lowered and there was no difference compared with that of pre-training. Compared with pre-training, urine calcium in the swimmers improved somewhat, but there was no obvious change either in the ratio between urine calcium and urine creatinine or between urinary hydroxyproline and urine creatinine. Discussion / Conclusions Long-time intensive training had a significant effect on bone metabolism of male swimmers with disabilities. This may be associated with the effect of the exercise on promoting the formation of bone and/or increasing bone metabolism and lower blood Ca level. The findings suggested that calcium should be supplemented in the food of male swimmers with disabilities in periods of intensive training.